PENGARUH METODE GENTLE BIRTH TERHADAP TINGKAT NYERI DAN DURASI KALA I PERSALINAN PADA IBU PRIMIPARA - Rezah Andriani; Selvy Apriani (LPPM Universitas Abdurrab, 2021)
According to World Health Organization (WHO), it is estimated that one woman dies in every minute, 1,400 in every day, or 500,000 in every year from pregnancy- and delivery-related complications. A large number of delivery-related complications reported in SDKI in 2017 are long delivery (41%). Both long delivery and pain that distress the mother during a delivery process is the reason for delivery trauma and increases in delivery by sectio caesarea operation. Due to a phenomenon of increasing trends in caesarea operation and other unnecessary medical interventions, there reemerges an awareness to back to a natural delivery concept that considers the whole aspects of human body holistically (called gentle birth).ÃƒÂ¢Ã¢â€šÂ¬Ã‚ÂGentle birthÃƒÂ¢Ã¢â€šÂ¬Ã‚Â is a serene, smooth, gentle delivery and utilizes all natural elements in human (body, mind, and soul). Currently, some alternative methods of delivery process with a gentle birth concept are developing, such as prental yoga and hypnobirthing relaxation. The objective of the present research is to analyze the effect of gentle birth method on the pain level and phase-I duration of delivery in primipara mother. The research is a quasi-experimental research with a post test control group design. Sampling was performed by a consecutive sampling up to the number of sample the researcher wanted has been met according to an inclusion criterion. The research result revealed that there was some significant average difference in the pain level and phase-I duration of delivery between the experimental and control groups. Expectantly, the research result contributes to midwifery science as an attempt to deliver a holistic delivery midwifery care (gentle birth) so as to relieve delivery-related pain and to shorten delivery duration. KEYWORDS: Gentle birth, prental yoga, hypnobirthing, delivery pain, delivery duration